Uji Toksisitas Ekstrak Pigmen Kasar Mikroalga Spirulina platensis Dengan Metode Uji Bslt (Brine Shrimp Lethality Test) - Rizkina, Rani Agustian; Yudiati, Ervia; Sedjati, Sri (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Spirulina platensis is a microalgae which rich of nutrients and has a potential extracts as an antioxidant, antimicrobial, antiviral, anti-inflamantory and antitumor. The aims of this research were to determine toxicity of methanol extract and crude pigment (methanol-acetone and diethyl ether fractions) of S. platensis against nauplii Artemia sp. aged 24 hour at 3rd instar as an antitumor. The aims of this research were to determine toxicity of methanol extract and crude pigment (methanol-acetone and diethyl ether fractions) of S. platensis against nauplii Artemia sp. The research was conducted in August-October 2011 at Microalgae Laboratory, Marine Station, Diponegoro University Teluk Awur Jepara. Toxicity test methanol and crude pigment extract calculated by LC50-24 hour with BSLT (Brine Shrimp Lethality Test) methodes and pigment analysis was carried out by TLC (Thin Layer Chromatography). The results of BSLT (Brine Shrimp Lethality Test) methanol extracts and crude pigment (methanol-acetone and diethyl ether fractions) showed that LC50-24 hour values of each extract methanol (446,68 ppm), crude pigment extract ethanol-acetone (134.9 ppm) and a crude fraction pigment extract diethyl ether (91.2 ppm). The crude pigment has a cytotoxic effect LC50-24 hours <1000 ppm showed that the extracts are toxic to nauplii Artemia sp. 24 hours, 3rd instar and has a potential antitumor compounds. The results of pigments identification showed contains carotenoids and chlorophylla.